Peningkatan Kemampuan Kognitif Melalui Penerapan Model Pembelajaran TGT Pada Siswa Sekolah Dasar - Hidayati Isnaini Safitri, Nur; Intan Syaputri, Widia (Faculty Of Education, 2025)
The background of this research is the low cognitive abilities of students in class IV UPT SDN 004 Langgini. This research aims to improve students' cognitive abilities through the application of Team Games Tournament learning capital in class IV UPT SDN 004 Langgini. This research is classroom action research carried out in 2 cycles and each cycle consists of 2 meetings. The subjects in this research were 12 students in class IV UPT SDN 004 Langgini, consisting of 5 male students and 7 female students. This research instrument consists of teacher activity observation sheets, student activity observation sheets, test sheets, and documentation width. Meanwhile, the data analysis techniques used are qualitative analysis and quantitative analysis. Based on the results of research carried out in 2 cycles, in cycle I, meeting 1, there were 6 students with a percentage of 50%, in cycle I, meeting 2, there were 8 students with a percentage of 66.67%, in cycle II, meeting 1, there were 9 people. students with a percentage of 75% and in cycle II meeting 2 there were 10 students with a percentage of 83.33%. Thus it can be concluded that through the application of the Team Games Tournament learning model it can improve the cognitive abilities of fourth grade students at State Elementary UPT SDN 004 Langgini.